2023
DOI: 10.1162/jocn_a_01956
|View full text |Cite
|
Sign up to set email alerts
|

Landmark-dependent Navigation Strategy Declines across the Human Life-Span: Evidence from Over 37,000 Participants

Abstract: Humans show a remarkable capacity to navigate various environments using different navigation strategies, and we know that strategy changes across the life span. However, this observation has been based on studies of small sample sizes. To this end, we used a mobile app-based video game (Sea Hero Quest) to test virtual navigation strategies and memory performance within a distinct radial arm maze level in over 37,000 participants. Players were presented with 6 pathways (3 open and 3 closed) and were required t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 77 publications
8
8
0
Order By: Relevance
“…By combining the NSQ with the RAM tests for this study we reveal, for this population, that landmark-counting strategies appear to be orthogonal to the survey-route dimension captured by the NSQ. Notably, the lack of a correlation between wayfinding inefficiency and the RAM measures in this small lab sample matches our recent report of an absence of correlation between these in an online sample of over 37,000 participants (West et al, 2023). The absence of a correlation of the PI measure and the other navigation tasks is notable in light of recent evidence that PI, rather than other spatial tests, might be particularly important for early detection of AD (Kunz et al, 2015; Bierbrauer et al, 2020; Newton et al, 2023).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…By combining the NSQ with the RAM tests for this study we reveal, for this population, that landmark-counting strategies appear to be orthogonal to the survey-route dimension captured by the NSQ. Notably, the lack of a correlation between wayfinding inefficiency and the RAM measures in this small lab sample matches our recent report of an absence of correlation between these in an online sample of over 37,000 participants (West et al, 2023). The absence of a correlation of the PI measure and the other navigation tasks is notable in light of recent evidence that PI, rather than other spatial tests, might be particularly important for early detection of AD (Kunz et al, 2015; Bierbrauer et al, 2020; Newton et al, 2023).…”
Section: Discussionsupporting
confidence: 90%
“…We found that those that used the landmark strategy on RAM levels performed significantly better on both RAM and wayfinding levels than those who used the counting strategy. This mirrors recent evidence from the large participant group of over 37,000 participants (West et al, 2023). By combining the NSQ with the RAM tests for this study we reveal, for this population, that landmark-counting strategies appear to be orthogonal to the survey-route dimension captured by the NSQ.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations